Kelvin probe force microscopy in liquid using electrochemical force microscopy - Collins, Liam; Jesse, Stephen; Kilpatrick, Jason I.; Tselev, Alexander; Okatan, M. Baris; Kalinin, Sergei V.; Rodriguez, Brian J. (Beilstein Journal of Nanotechnology, 2015)
Conventional closed loop-Kelvin probe force microscopy (KPFM) has emerged as a powerful technique for probing electric and transport phenomena at the solid–gas interface. The extension of KPFM capabilities to probe electrostatic and electrochemical phenomena at the solid–liquid interface is of interest for a broad range of applications from energy storage to biological systems. However, the operation of KPFM implicitly relies on the presence of a linear lossless dielectric in the probe–sample gap, a condition which is violated for ionically-active liquids (e.g., when diffuse charge dynamics are present). Here, electrostatic and electrochemical measurements are demonstrated in ionically-active (polar isopropanol, milli-Q water and aqueous NaCl) and ionically-inactive (non-polar decane) liquids by electrochemical force microscopy (EcFM), a multidimensional (i.e., bias- and time-resolved) spectroscopy method. In the absence of mobile charges (ambient and non-polar liquids), KPFM and EcFM are both feasible, yielding comparable contact potential difference (CPD) values. In ionically-active liquids, KPFM is not possible and EcFM can be used to measure the dynamic CPD and a rich spectrum of information pertaining to charge screening, ion diffusion, and electrochemical processes (e.g., Faradaic reactions). EcFM measurements conducted in isopropanol and milli-Q water over Au and highly ordered pyrolytic graphite electrodes demonstrate both sample- and solvent-dependent features. Finally, the feasibility of using EcFM as a local force-based mapping technique of material-dependent electrostatic and electrochemical response is investigated. The resultant high dimensional dataset is visualized using a purely statistical approach that does not require a priori physical models, allowing for qualitative mapping of electrostatic and electrochemical material properties at the solid–liquid interface.
Keywords: diffuse charge dynamics; double layer charging; electrochemical force microscopy; electrochemistry; Kelvin probe force microscopy

Introduction to Surface Chemistry and Catalysis - Somorjai, G. A.; Li, Y. (John Wiley & Sons, 2010)

Physical Chemistry of Surfaces - Adamson, A. W.; Gast, A. P. (Wiley & Sons, 1967)

(untitled) - Zaera, F. (Chem. Rev., 2012)

(untitled) - Bazant, M. Z.; Kilic, M. S.; Storey, B. D.; Ajdari, A. (Adv. Colloid Interface Sci., 2009)

(untitled) - van Soestbergen, M.; Biesheuvel, P. M.; Bazant, M. Z. (Phys. Rev. E, 2010)

(untitled) - Kilic, M. S.; Bazant, M. Z.; Ajdari, A. (Phys. Rev. E, 2007)

(untitled) - Kilic, M. S.; Bazant, M. Z.; Ajdari, A. (Phys. Rev. E, 2007)

(untitled) - Storey, B. D.; Edwards, L. R.; Kilic, M. S.; Bazant, M. Z. (Phys. Rev. E, 2008)

(untitled) - Bazant, M. Z.; Kilic, M. S.; Storey, B. D.; Ajdari, A. (New J. Phys., 2009)

(untitled) - Biesheuvel, P. M.; Fu, Y.; Bazant, M. Z. (Phys. Rev. E, 2011)

Scanning Electrochemical Microscopy - Bard, A. J.; Mirkin, M. V. (CRC Press, 2012)

(untitled) - Balke, N.; Bonnell, D.; Ginger, D. S.; Kemerink, M. (MRS Bull., 2012)

(untitled) - Black, J.; Strelcov, E.; Balke, N.; Kalinin, S. V. (Electrochem. Soc. Interface, 2014)

(untitled) - Strelcov, E.; Kim, Y.; Jesse, S.; Cao, Y.; Ivanov, I. N.; Kravchenko, I. I.; Wang, C.-H.; Teng, Y.-C.; Chen, L.-Q.; Chu, Y. H.; Kalinin, S. V. (Nano Lett., 2013)

(untitled) - Balke, N.; Jesse, S.; Morozovska, A.; Eliseev, E.; Chung, D. W.; Kim, Y.; Adamczyk, L.; Garcia, R. E.; Dudney, N.; Kalinin, S. V. (Nat. Nanotechnol., 2010)

(untitled) - Martin, Y.; Abraham, D. W.; Wickramasinghe, H. K. (Appl. Phys. Lett., 1988)

(untitled) - Terris, B. D.; Stern, J. E.; Rugar, D.; Mamin, H. J. (Phys. Rev. Lett., 1989)

(untitled) - Kalinin, S. V.; Bonnell, D. A. (Phys. Rev. B, 2002)

(untitled) - Kumar, A.; Ciucci, F.; Morozovska, A. N.; Kalinin, S. V.; Jesse, S. (Nat. Chem., 2011)

(untitled) - Nonnenmacher, M.; O'Boyle, M. P.; Wickramasinghe, H. K. (Appl. Phys. Lett., 1991)

Scanning Probe Microscopy in Nanoscience and Nanotechnology 3 - Weber, S. A. L.; Butt, H. J.; Berger, R. (Electrical Characterization of Solar Cell Materials Using Scanning Probe Microscopy, 2013)

(untitled) - Liscio, A.; De Luca, G.; Nolde, F.; Palermo, V.; Müllen, K.; Samorì, P. (J. Am. Chem. Soc., 2008)

(untitled) - Loppacher, C.; Zerweck, U.; Teich, S.; Beyreuther, E.; Otto, T.; Grafström, S.; Eng, L. M. (Nanotechnology, 2005)

Applications of Ferroelectrics held jointly with 2012 European Conference on the Applications of Polar Dielectrics and 2012 International Symp Piezoresponse Force Microscopy and Nanoscale Phenomena in Polar Materials (ISAF/ECAPD/PFM) - Collins, L.; Kilpatrick, J. I.; Bhaskaran, M.; Sriram, S.; Weber, S.; Jarvis, S.; Rodriguez, B. (Dual Harmonic Kelvin Probe Force Microscopy for Surface Potential Measurements of Ferroelectrics, 2012 Intl Symp, 2012)

(untitled) - Kalinin, S. V.; Bonnell, D. A. (Phys. Rev. B, 2001)

(untitled) - Kalinin, S. V.; Bonnell, D. A. (J. Appl. Phys., 2000)

(untitled) - Lubarsky, G.; Shikler, R.; Ashkenasy, N.; Rosenwaks, Y. (J. Vac. Sci. Technol., B, 2002)

(untitled) - Bocquet, F.; Nony, L.; Loppacher, C.; Glatzel, T. (Phys. Rev. B, 2008)

(untitled) - Egberts, P.; Filleter, T.; Bennewitz, R. (Nanotechnology, 2009)

(untitled) - Enevoldsen, G. H.; Glatzel, T.; Christensen, M. C.; Lauritsen, J. V.; Besenbacher, F. (Phys. Rev. Lett., 2008)

(untitled) - Okamoto, K.; Yoshimoto, K.; Sugawara, Y.; Morita, S. (Appl. Surf. Sci., 2003)

(untitled) - Mohn, F.; Gross, L.; Moll, N.; Meyer, G. (Nat. Nanotechnol., 2012)

(untitled) - Polak, L.; de Man, S.; Wijngaarden, R. J. (Rev. Sci. Instrum., 2014)

(untitled) - Collins, L.; Kilpatrick, J. I.; Weber, S. A.; Tselev, A.; Vlassiouk, I.; Ivanov, I.; Jesse, S.; Kalinin, S.; Rodriguez, B. (Nanotechnology, 2013)

(untitled) - Barbet, S.; Popoff, M.; Diesinger, H.; Deresmes, D.; Théron, D.; Mélin, T. (J. Appl. Phys., 2014)

(untitled) - Sugimura, H.; Ishida, Y.; Hayashi, K.; Takai, O.; Nakagiri, N. (Appl. Phys. Lett., 2002)

(untitled) - Bazant, M. Z.; Thornton, K.; Ajdari, A. (Phys. Rev. E, 2004)

(untitled) - Collins, L.; Jesse, S.; Kilpatrick, J. I.; Tselev, A.; Varenyk, O.; Okatan, M. B.; Weber, S. A. L.; Kumar, A.; Balke, N.; Kalinin, S. V. (Nat. Commun., 2014)

(untitled) - Domanski, A. L.; Sengupta, E.; Bley, K.; Untch, M. B.; Weber, S. A. L.; Landfester, K.; Weiss, C. K.; Butt, H.-J.; Berger, R. (Langmuir, 2012)

(untitled) - Kobayashi, N.; Asakawa, H.; Fukuma, T. (J. Appl. Phys., 2011)

(untitled) - Kobayashi, N.; Asakawa, H.; Fukuma, T. (Rev. Sci. Instrum., 2012)

(untitled) - Kobayashi, N.; Asakawa, H.; Fukuma, T. (Rev. Sci. Instrum., 2010)

(untitled) - Collins, L.; Kilpatrick, J. I.; Vlassiouk, I. V.; Tselev, A.; Weber, S. A.; Jesse, S.; Kalinin, S. V.; Rodriguez, B. J. (Appl. Phys. Lett., 2014)

(untitled) - Guo, S.; Kalinin, S. V.; Jesse, S. (Nanotechnology, 2012)

(untitled) - Takeuchi, O.; Ohrai, Y.; Yoshida, S.; Shigekawa, H. (Jpn. J. Appl. Phys., Part 1, 2007)

(untitled) - Cherniavskaya, O.; Chen, L.; Weng, V.; Yuditsky, L.; Brus, L. E. (J. Phys. Chem. B, 2003)

(untitled) - Fumagalli, L.; Esteban-Ferrer, D.; Cuervo, A.; Carrascosa, J. L.; Gomila, G. (Nat. Mater., 2012)

(untitled) - Fumagalli, L.; Gramse, G.; Esteban-Ferrer, D.; Edwards, M.; Gomila, G. (Appl. Phys. Lett., 2010)

(untitled) - Gramse, G.; Edwards, M. A.; Fumagalli, L.; Gomila, G. (Appl. Phys. Lett., 2012)

(untitled) - Gramse, G.; Edwards, M.; Fumagalli, L.; Gomila, G. (Nanotechnology, 2013)

(untitled) - Pashley, R. M.; Rzechowicz, M.; Pashley, L. R.; Francis, M. J. (J. Phys. Chem. B, 2005)

(untitled) - Kim, Y.; Kumar, A.; Ovchinnikov, O.; Jesse, S.; Han, H.; Pantel, D.; Vrejoiu, I.; Lee, W.; Hesse, D.; Alexe, M.; Kalinin, S. V. (ACS Nano, 2011)

(untitled) - Arruda, T. M.; Kumar, A.; Kalinin, S. V.; Jesse, S. (Nano Lett., 2011)

(untitled) - Raiteri, R.; Butt, H.-J. (J. Phys. Chem., 1995)

(untitled) - Umeda, K.; Kobayashi, K.; Oyabu, N.; Hirata, Y.; Matsushige, K.; Yamada, H. (J. Appl. Phys., 2014)

(untitled) - Nicholson, R. S. (Anal. Chem., 1965)

Electrochemical Methods: Fundamentals and Applications - Bard, A. J.; Faulkner, L. R. (Wiley, 1980)

(untitled) - Butt, H.-J. (Biophys. J., 1991)

(untitled) - Sounart, T. L.; Michalske, T. A.; Zavadil, K. R. (J. Micromech. Microeng., 2005)

Principal component analysis - Jolliffe, I. (John Wiley & Sons, Ltd, 2005)

(untitled) - Strelcov, E.; Belianinov, A.; Hsieh, Y.-H.; Jesse, S.; Baddorf, A. P.; Chu, Y.-H.; Kalinin, S. V. (ACS Nano, 2014)